On two species of the alpheid shrimp genus Salmoneus Holthuis, 1955 from Kuwait, one of them new to science (Malacostraca: Decapoda: Caridea) - Anker, Arthur; Al-Kandari, Manal; de Grave, Sammy (Zootaxa, 2020)
The alpheid genus Salmoneus Holthuis, 1955 is reported from Kuwait for the first time, with two species. One species, Salmoneus ikaros sp. nov., is described based on a single specimen from Failaka Island, extracted from the burrow of the callianassid ghost-shrimp Balsscallichirus masoomi (Tirmizi, 1970), together with the host. The new species is characterised by its peculiar eyes, which together with other characters separate it from all previously described species of Salmoneus. The second species, Salmoneus gracilipes Miya, 1972, is reported from Kuwait based on three specimens from two different localities and different habitats. Two specimens were found under coral rocks at a depth of about 7 m off Kubbar Island, whereas the third specimen was extracted from the burrow of the echiuran worm, Listriolobus cf. brevirostris Chen & Yeh, 1958, at the type locality of S. ikaros sp. nov. at Failaka Island. Material identified as S. gracilipes from across its wide distribution range appears to be morphologically heterogeneous, possibly containing more than one species, and thus will need further studies.